(untitled) (Scientific journal of the Fergana State University, 2025)
Artificial Intelligence (AI) is becoming a key area of development. This article is devoted to analyzing the role of pedagogical strategies in the successful implementation of AI technologies in the educational process. The study used methods of analyzing scientific literature, surveys, interviews with experts and studying practical cases. Key findings include identifying the significance of adapting instructional materials, increasing student motivation, and supporting teachers in the face of automation. Challenges related to ethical issues, educator training and cultural differences are also discussed. It is concluded that well-designed pedagogical strategies are the foundation for successful AI integration, facilitating the harmonious interaction of technology and traditional learning. The article offers recommendations for educator training, national strategies, and ethical considerations. These measures will create effective and equitable educational environments that can meet the needs of students and teachers in the digital age.